Contribuições das reflexões do Círculo de Bakhtin para o estudo e prática da tradução: uma análise do datiloscrito de Clarice Lispector da peça The member of the wedding - Oliveira, Eneida Gomes Nalini de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Besides being a chronicler, a novelist and a playwright, Clarice Lispector also worked as a translator and as part of this last job she left the unfinished datiloscrito of the play The member of the wedding (1961). The play was originally written by Carson McCullers. Without there being any publication, of this work, it is part of Casa de Rui Barbosa Foundation and it presents handwritten interventions - questions, possible changings, deletions and comments, which explains her tradutological process. The aim of this paper is to analyze the translation according to Bakhtin Circle's reflections, establishing dialogues between the original text, the translation itself and what we call retranslation, in which there are handwritten interventions. The analysis of translation process of these two versions led us to accomplish two other translations from the original text - a literal translation and a literary translation - in order to have two references of analytical comparison. This investigation is performed through dialogism and ideological interrelation, aesthetic and contextual between the writers Clarice Lispector and Carson McCullers and their productions. In this sense, we have the support of linguistc assumptions, starting in Saussure, Benveniste and Bakhtin's contributions. In addition to Bakhtin's contributions and the translation studies, the chronicle Traduzir procurando não trair published in Revista Jóia, in 1968 is important in the analysis because Clarice Lispector reflects upon the practice of translation, registering personal opinions about the act of translating. As a result, we verify the translator's presence as a thinking subject, showing the style and authorship in the translation, solving linguistcis variation presents in the original text as well as resolving problems of the discursive genre. There is room of intermediation between the original text and its translation that allows changes...

Além de cronista, romancista e dramaturga, Clarice Lispector trabalhou também como tradutora e, desse último ofício, deixou o datiloscrito da peça The member of the wedding (1946), de Carson McCullers, inacabado. Sem que houvesse nenhuma publicação dessa obra, o datiloscrito integra o espólio da escritora na Fundação Casa de Rui Barbosa, e apresenta intervenções manuscritas - dúvidas, possíveis alterações, rasuras e comentários, que explicitam o processo tradutológico. O objetivo deste trabalho é analisar esse processo a partir das reflexões do Círculo de Bakhtin, estabelecendo diálogos entre o texto fonte, a tradução datilografada e o que chamamos de retradução, em que são incluídas as intervenções manuscritas. A análise do processo tradutológico dessas duas versões nos levou a realizar duas outras traduções a partir do texto fonte - uma tradução literal e uma tradução literária - a fim de termos outros dois referenciais de comparação analítica. A investigação se dá por meio do diálogo e da inter-relação ideológica, estética e contextual entre as escritoras, Carson McCullers e Clarice Lispector e suas respectivas obras. Neste sentido, apoiamo-nos em pressupostos linguísticos começando por Saussure, passando por Benveniste para chegarmos às contribuições bakhtinianas. Além das contribuições linguísticas bakhtinianas e dos estudos de tradução, a crônica Traduzir procurando não trair, publicada na Revista Jóia, em 1968, é fundamental nas análises desenvolvidas, pois nela a cronista Clarice Lispector reflete sobre a prática de tradução, registrando opiniões pessoais e ponderações sobre o ato de traduzir. Como resultado verificamos a presença do tradutor como um sujeito situado, deixando marcas de seu estilo em sua autoria tradutória, resolvendo as questões de variações linguísticas presentes no texto de chegada, bem como solucionando problemas do âmbito da...
Keywords: Bakhtin, M. M. (Mikhail Mikhailovich) 1895-1975; Lispector, Clarice 1920-1977; Dialogismo (Análise literária); Traduções; Translations